The prevalence of serological markers of viral hepatitis among labor migrants arriving in the Russian Federation - N. D. AlSalih; D. A. Sychev; I. A. Potemkin; K. K. Kyuregyan; M. I. Mikhailov (Журнал инфектологии)
Aim. To determine of the prevalence of viral hepatitis A, E, B, C and D markers in migrant workers.Materials and methods. Blood serum samples from 1,333 migrant workers recently arrived in Russia from Uzbekistan (n = 464), Tajikistan (n = 415), Ukraine (n = 308) and Moldova (n = 146) were analyzed. Anti-HAV IgG, anti-HEV IgM and IgG, HBsAg, anti-HBV and anti-HCV were tested using commercial ELISA tests.Results. The frequency of HBsAg detection was significantly higher among migrants from Tajikistan and Uzbekistan (5,3% and 5,2%, respectively) compared to migrants from Ukraine (1,0%) and Moldova (3,4%). No anti-HDV was detected in any positive HBsAg sample. The rate of anti-HCV detection was high regardless of the country of origin: 4,5% (Uzbekistan), 4.8% (Tajikistan), 3,9% (Ukraine), 4,8% (Moldova). Anti-HEV IgG was significantly higher in migrants from Uzbekistan and Tajikistan compared to those from Ukraine and Moldova (25,4% and 43,1%, vs. 7,8% and 12,3%, respectively, p <0,05). Anti-HEV IgM, indicative of current or recent infection, was detected in migrants from Uzbekistan, Tajikistan, Ukraine and Moldova with similar frequency – 3,9%, 7,8%, 5,8% and 6,8%, respectively. AntiHAV IgG positivity rate was significantly lower in migrants from Ukraine compared to those from Moldova, Uzbekistan and Tajikistan (70,1% versus 91,8%, 98,7%, 99,8%, respectively, p <0,05).Conclusion. The high prevalence of hepatitis B and C serologic markers in labor migrants, as well as anti-HEV IgM, suggests a high probability of the importation of HCV, HBV and HEV in the Russian Federation. Thus, inclusion of hepatitis B, C and E testing into routine screening of labor migrants might be beneficial.